Using Activity Theory to Examine How Teachers' Lesson Plans Meet Students' Learning Needs. Issue 1 (2nd January 2018) - Chizhik, Estella Williams; Chizhik, Alexander Williams
ABSTRACT: How is lesson planning useful? This research study used Cultural Historical Activity Theory and intersubjectivity to answer this questions. This research explored to what extent teacher candidates' lesson plans (i.e., alignment among objectives, assessment, and instruction), and analyses of assessment data mediate their thinking about students' learning needs. Four to five daily lesson plans with corresponding videos and commentaries from 10 elementary school (K–6) teacher candidates were used in this study. Qualitative analyses revealed that teacher candidates seldom considered their students' learning needs and seldom anticipated how instructional activities facilitated students' thinking. One teacher candidate, however, used assessment data to consider students' learning needs and to plan future lessons to meet students' learning needs. The implication of research findings suggest that teacher education programs must improve in developing teacher candidates' skills of aligning lesson plan features and using assessment data as tools to mediate their thinking about students' learning needs.